Epigenetic Mechanisms Mediating Cell State Transitions in Chondrocytes. (2nd March 2021) - Wuelling, Manuela; Neu, Christoph; Thiesen, Andrea M; Kitanovski, Simo; Cao, Yingying; Lange, Anja; Westendorf, Astrid M; Hoffmann, Daniel; Vortkamp, Andrea
ABSTRACT: Epigenetic modifications play critical roles in regulating cell lineage differentiation, but the epigenetic mechanisms guiding specific differentiation steps within a cell lineage have rarely been investigated. To decipher such mechanisms, we used the defined transition from proliferating (PC) into hypertrophic chondrocytes (HC) during endochondral ossification as a model. We established a map of activating and repressive histone modifications for each cell type. ChromHMM state transition analysis and Pareto‐based integration of differential levels of mRNA and epigenetic marks revealed that differentiation‐associated gene repression is initiated by the addition of H3K27me3 to promoters still carrying substantial levels of activating marks. Moreover, the integrative analysis identified genes specifically expressed in cells undergoing the transition into hypertrophy. Investigation of enhancer profiles detected surprising differences in enhancer number, location, and transcription factor binding sites between the two closely related cell types. Furthermore, cell type–specific upregulation of gene expression was associated with increased numbers of H3K27ac peaks. Pathway analysis identified PC‐specific enhancers associated with chondrogenic genes, whereas HC‐specific enhancers mainly control metabolic pathways linking epigenetic signature to biological functions. Since HC‐specific enhancers show a higher conservation in postnatal tissues, the switch to metabolic pathways seems to be a hallmark of differentiated tissues. Surprisingly, the analysis of H3K27ac levels at super‐enhancers revealed a rapid adaption of H3K27ac occupancy to changes in gene expression, supporting the importance of enhancer modulation for acute alterations in gene expression. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR). Abstract : Model depicting the epigenetic mechanisms regulating cell state transitions. Proliferating (PC) and hypertrophic chondrocytes (HC) were isolated from embryonic limbs using flow cytometry for ChIP‐seq and laser‐microdissection for RNA‐seq. Prehypertrophic chondrocytes (PHC) were included in different cell populations. Comparison of the epigenetic pattern between cell types indicates that gene repression in HC is initiated by the gain of H3K27me3 at promoters still decorated with declining levels of activating marks. Cell type–specific enhancers show a rapid adaption of H3K27ac peaks to differential gene expression. Whereas PC‐specific enhancers are associated with chondrogenic genes, HC‐specific enhancers regulate metabolic pathways. H3K4me3: light blue; H3K9ac : dark green; H3K27ac : light green; H3K36me3   : dark blue; H3K27me3  : red.